Cytotoxic triterpenoid saponins from the defatted seeds of Camellia oleifera Abel. Issue 5 (4th May 2018) - Fu, Hui-Zheng; Wan, Kai-Hua; Yan, Qing-Wei; Zhou, Guo-Ping; Feng, Tong-Tong; Dai, Mian; Zhong, Rui-Jian
Abstract: Five new oleanane-type triterpenoid saponins, oleiferasaponins D1 –D5 (1 –5 ), were isolated from the defatted seeds of Camellia oleifera Abel. Their structures were elucidated by spectroscopic and chemical methods. The cytotoxic activities of compounds1 –5 were evaluated against five human tumor cell lines (HCT-116, HepG2, BGC-823, NCI-H1650, and A2780). Compounds1 –2 exhibited cytotoxic activity against five human cancer cell lines, with IC50 values ranging from 3.31 to 10.23 μM. Compounds3 –5 showed moderate cytotoxic activities toward the tested cell lines. Abstract :